Analisis Kebutuhan Layanan dan Fasilitas Eksisting Transportasi Ramah Lingkungan Dengan Kebutuhan Perjalanan (Studi Kasus: Pegawai di Lingkungan Pemerintah Kota Tanjungpinang) - Hayuningtyas, Rachmania; Irawan, Muhammad Zudhy; Dewanti, Dewanti (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
State employees of Tanjungpinang consists of 4,303 people whose origins and destinations are spread throughout the city. This is the reason for the high travel demand where private vehicles are still superior to the other modes of choice. This adds to problems in environmental aspects, especially the contributors to air pollution and noise on the road. This study uses a quantitative method with descriptive analysis and spatial analysis. Descriptive analysis is used to identify existing employee travel characteristics. The graphic display presented in the results of the descriptive analysis aims to make it easier to explain the results of the analysis of the formation of zones, the number of trips in each zone, as well as the focus services and existing facilities. Spatial analysis is used to point to the edge of the location of existing facilities, and the ease of origin and destination of employee travel. The results of the study indicate that the current supply of services and facilities has not been able to accommodate the travel demand of state employees. The supply of transport services and facilities is still lacking because they only serve and available in several sub-districts which are the points of origin and destinations travel for employees. This caused low interest of employees by using green transport whose origin and destination areas are not covered and crossed by services. Therefore, it is necessary to request institutional-based travel demand management to encourage employees to travel using green transport in the form of policies, coordination, and cooperation within the internal scope of the Tanjungpinang city government.